2022
DOI: 10.21037/tp-22-113
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ knowledge and attitude and behavior toward autism: a survey of Chinese families having children with autism spectrum disorder

Abstract: Background: In recent years, parent-mediated intervention for children with autism spectrum disorder (ASD) has increased. Therefore, implementing effective parent training programs for parents of children with autism is of paramount importance, particularly in low-and middle-income countries. However, little is known about the status of and gaps in parents' knowledge on ASD, which may hinder the development of valid parental training programs. Herein, we aimed at exploring the status of Chinese parents' knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In addition, parents are concerned that their lack of experience and access to the most recent information about the illness might impede their children’s rehabilitation 51 . The situation agrees with the findings of Wang et al We claim that through the engagement of relevant national policies, we must develop a service system for the caregiving obligations of the autistic group and provide caregivers with psychological support in the form of social solidarity 52 . Let the state shoulder the rehabilitation training system for autistic groups, and alleviate a portion of the load of autistic caretakers 53 .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, parents are concerned that their lack of experience and access to the most recent information about the illness might impede their children’s rehabilitation 51 . The situation agrees with the findings of Wang et al We claim that through the engagement of relevant national policies, we must develop a service system for the caregiving obligations of the autistic group and provide caregivers with psychological support in the form of social solidarity 52 . Let the state shoulder the rehabilitation training system for autistic groups, and alleviate a portion of the load of autistic caretakers 53 .…”
Section: Discussionsupporting
confidence: 89%
“…The questionnaire survey for the quantitative analysis consisted of forty questions that comprehensively covered the primary design aspects that need to be considered, in terms of light and color perceptions, before designing interior spaces intended for autistic children. The questionnaire was carefully designed in a lucid and straightforward format from the literature (67)(68)(69)(70)(71)(72)(73). The questionnaire was fine-tuned further in consultation with the therapists.…”
Section: Data Collectionmentioning
confidence: 99%
“…The correlation between parents' knowledge and caregiving practices emphasizes the importance of ongoing support and training. Wang et al (2022) reported the importance of increasing parents' awareness about ASD as a crucial step in assisting them in caring for their children. Nurses have the capacity to play a significant role in delivering continuous education and guidance to parents, thereby promoting consistent and evidence-based care practices (Fraatz and Durand , 2021).…”
Section: Discussionmentioning
confidence: 99%